1999
DOI: 10.1002/clc.4960220709
|View full text |Cite
|
Sign up to set email alerts
|

Examining the psychosocial impact of implantable cardioverter defibrillators: A literature review

Abstract: SummaryBackground: The implantable cardioverter defibrillator (ICD) has proven to be superior to medications in treating potentially life-threatening ventricular arrhythmias, resulting in reduced mortality rates. Despite the number of patients receiving this therapy, its psychosocial impact is not well understood.Hyporhesis: The purposes of this paper are (1) to review the available literature documenting the psychosocial impact of the ICD on patients, (2) to hypothesize possible mechanisms for this psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(37 citation statements)
references
References 30 publications
0
35
0
2
Order By: Relevance
“…ICD shocks have also been associated with independent predictors of mortality in the large ALTITUDE registry of 3809 ICD recipients and in a metaanalysis of ICD trials in which ATP was applied [155,157]. Emotional morbidities associated with ICD shocks are well recognized and include anxiety, depression, and posttraumatic stress disorders [174][175][176]. Phantom shocks can result from fear and/or anxiety and have a reported incidence of 5% in a European study of ICD recipients over 35 months of follow-up [177].…”
Section: Unintended Consequences Of Icd Therapy and Icd Therapy Progrmentioning
confidence: 99%
“…ICD shocks have also been associated with independent predictors of mortality in the large ALTITUDE registry of 3809 ICD recipients and in a metaanalysis of ICD trials in which ATP was applied [155,157]. Emotional morbidities associated with ICD shocks are well recognized and include anxiety, depression, and posttraumatic stress disorders [174][175][176]. Phantom shocks can result from fear and/or anxiety and have a reported incidence of 5% in a European study of ICD recipients over 35 months of follow-up [177].…”
Section: Unintended Consequences Of Icd Therapy and Icd Therapy Progrmentioning
confidence: 99%
“…E. Ford & Kamerow, 1989). Similarly, the rates of depression and anxiety in patients with ICDs are high, but comparable to other cardiac disease populations(Sears, Todaro, Lewis, Sotile, & Conti, 1999; W. Whang et al, 2005) found that 14% of a sample of ICD patients were categorized as mildly depressed, while 3.9% were moderately to severely depressed, with depression significantly predicting risk for an ICD shock.…”
mentioning
confidence: 56%
“…In particular, more experiences of anxiety, fatigue, and confusion and fewer experiences of energy increased the possibility of an arrhythmia event. Anxiety symptoms may be the most universal yet debilitating experience of the ICD patient; 24–87% of ICD recipients experienced increased anxiety as a result of ICD implantation, with approximately 13–38% meeting criteria for clinically significant anxiety disorders (Sears et al, 1999). Individuals with insomnia may also experience impaired daytime functioning, such as fatigue and excessive daytime sleepiness (K.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable body of evidence gathered from ICD recipients suggests that psychosocial factors, including depression [33], anxiety [34-37] and personality [38,39] are associated with patient reported outcomes. Patients who receive shocks from the ICD report reductions in health-related quality of life (HRQL) [40,41].…”
Section: Introductionmentioning
confidence: 99%